The glutathione redox system is essential to prevent ferroptosis caused by impaired lipid metabolism in clear cell renal cell carcinoma - Miess, Heike; Dankworth, Beatrice; Gouw, Arvin M.; Rosenfeldt, Mathias; Schmitz, Werner; Jiang, Ming; Saunders, Becky; Howell, Michael; Downward, Julian; Felsher, Dean W.; Peck, Barrie; Schulze, Almut (Oncogene, 2018)
Metabolic reprogramming is a prominent feature of clear cell renal cell carcinoma (ccRCC). Here we investigated metabolic dependencies in a panel of ccRCC cell lines using nutrient depletion, functional RNAi screening and inhibitor treatment. We found that ccRCC cells are highly sensitive to the depletion of glutamine or cystine, two amino acids required for glutathione (GSH) synthesis. Moreover, silencing of enzymes of the GSH biosynthesis pathway or glutathione peroxidases, which depend on GSH for the removal of cellular hydroperoxides, selectively reduced viability of ccRCC cells but did not affect the growth of non-malignant renal epithelial cells. Inhibition of GSH synthesis triggered ferroptosis, an iron-dependent form of cell death associated with enhanced lipid peroxidation. VHL is a major tumour suppressor in ccRCC and loss of VHL leads to stabilisation of hypoxia inducible factors HIF-1α and HIF-2α. Restoration of functional VHL via exogenous expression of pVHL reverted ccRCC cells to an oxidative metabolism and rendered them insensitive to the induction of ferroptosis. VHL reconstituted cells also exhibited reduced lipid storage and higher expression of genes associated with oxidiative phosphorylation and fatty acid metabolism. Importantly, inhibition of β-oxidation or mitochondrial ATP-synthesis restored ferroptosis sensitivity in VHL reconstituted cells. We also found that inhibition of GSH synthesis blocked tumour growth in a MYC-dependent mouse model of renal cancer. Together, our data suggest that reduced fatty acid metabolism due to inhibition of β-oxidation renders renal cancer cells highly dependent on the GSH/GPX pathway to prevent lipid peroxidation and ferroptotic cell death.